(untitled) (Bangladesh Journal of Medical Science, 2015)
Ibn Sina is one of the famous physicians of Muslim era. He is accepted as Physician par excellence. In his magnum opus, Al-Qanoon, he has collected all the knowledge of medicine from Hindu, Greek and Islamic sources known in tenth-century to eleventh centuries. It includes principles of surgery as well. Though we are not sure how much surgery he did himself as part of his memoirs are lost but he gives the idea of practice of Surgery of the period. In addition to anatomy, physiology and pathology he goes in the management of most surgical problems from head to toe. He is the first to describe the antiseptic properties of wine. We can also attribute to him the first description of Bennets fracture and his description of late splintage of fractures, now we now know as described by George Perkins. He had a great influence on the practice of medicine in the later centuries. Bangladesh Journal of Medical Science Vol.14(3) 2015 p.217-220